A study of superplasticity in Ti-6Al-4V: characterisation, modelling and applications - Martinez, E (2015)
Superplasticity is vital in many industries - medical, defense, aerospace, transport and sports amongst others -- for the fabrication of metallic components of complex geometry. The inherent peculiarity of the effect has kept theorists fascinated for many years. But significant controversy exists concerning the exact deformation mechanisms which are operative. In particular, precise details of the accommodation mechanics - whether those are diffusion, dislocation-accommodated, a combination of both or some sort of cooperative grain boundary sliding - are still matter of debate. In this thesis, superplasticity is first experimentally studied under constant strain-rate tensile conditions; this has allowed the regime of superplasticity to be pinpointed and it forms the basis of the computational material model. In addition, a method for the rapid quantification of superplastic properties using sub-scale specimens is presented: the approach is validated and then applied to a series of different titanium alloys. Results allowed to assess critically the main factors influencing superplasticity in titanium alloys. For the elucidation of the accommodation mechanisms accompanying grain boundary sliding during superplasticity, surface observations are carried out. For this, an in-situ scanning electron microscope testing module is employed. Different regimes of the phenomenon in the Ti-6Al-4V alloy are targeted: results provided important details of the mechanics at the grain level. For design purposes, this understanding is translated into validated material laws which are accurate and which capture the relevant phenomena. Microstructurally explicit material laws are proposed based upon the micromechanical modes of deformation which are shown to be operating with aim of incorporating those into the finite element analysis of superplastic forming. In the final part of the thesis, modelling is used to simulate an industrially-relevant manufacturing process which exploits superplasticity: the construction of hollow wide-chord fan blades which are of significant importance for the aerospace sector. The modelling is used to highlight the importance of microstructurally-based models and their influence on processing optimisation.